2020
DOI: 10.1007/jhep08(2020)143
|View full text |Cite
|
Sign up to set email alerts
|

Analytic bootstrap and Witten diagrams for the ABJM Wilson line as defect CFT1

Abstract: We study local operator insertions on 1/2-BPS line defects in ABJM theory. Specifically, we consider a class of four-point correlators in the CFT 1 with SU(1, 1|3) superconformal symmetry defined on the 1/2-BPS Wilson line. The relevant insertions belong to the short supermultiplet containing the displacement operator and correspond to fluctuations of the dual fundamental string in AdS 4 × CP 3 ending on the line at the boundary. We use superspace techniques to represent the displacement supermultiplet and we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 88 publications
2
54
0
1
Order By: Relevance
“…The action of Q + on Q can similarly be read from (D.15), but it misses the descendant. These are fixed instead by requiring closure under the Jacobi identity as in (3.6) (see also for instance the discussion in section 2 of [74]).…”
Section: Jhep03(2021)261mentioning
confidence: 99%
“…The action of Q + on Q can similarly be read from (D.15), but it misses the descendant. These are fixed instead by requiring closure under the Jacobi identity as in (3.6) (see also for instance the discussion in section 2 of [74]).…”
Section: Jhep03(2021)261mentioning
confidence: 99%
“…In principle one can do explicit perturbative JHEP04(2021)167 calculations as in [43], however it is perhaps simpler to set up a bootstrap problem and attempt to solve it using the technology of inversion formulas [45,46]. One could also concentrate exclusively on three dimensions and apply the numerical bootstrap on the line, analogous to what was done for the twist defect in the 3d Ising model [43] (the 1d bootstrap for superconformal line defects has been studied in [60][61][62]).…”
Section: Discussionmentioning
confidence: 99%
“…Defect conformal field theories supported on the 1/2 BPS Wilson line have been studied in four-dimensional N = 4 SYM [48,49] and its topological sector has been extensively studied in a series of papers [50][51][52]. The defect conformal field theory related to the 1/2 BPS Wilson line in ABJ(M) theory has been examined in [53], where it has been shown that, at variance with the four-dimensional case, the displacement supermultiplet does not admit a topological sector. Because the relevant symmetry is exactly su(1, 1|3) ⊕ u(1) b we expect that an explicit representation of the topological operators can be constructed, although in terms of supermatrices, as done in [53] for the displacement supermultiplet.…”
Section: Jhep06(2021)091mentioning
confidence: 99%
“…The defect conformal field theory related to the 1/2 BPS Wilson line in ABJ(M) theory has been examined in [53], where it has been shown that, at variance with the four-dimensional case, the displacement supermultiplet does not admit a topological sector. Because the relevant symmetry is exactly su(1, 1|3) ⊕ u(1) b we expect that an explicit representation of the topological operators can be constructed, although in terms of supermatrices, as done in [53] for the displacement supermultiplet. Work in this direction is in progress [41].…”
Section: Jhep06(2021)091mentioning
confidence: 99%